Increasing Evidence That Irritable Bowel Syndrome and Functional Gastrointestinal Disorders Have a Microbial Pathogenesis - Carco, Caterina; Young, Wayne; Gearry, Richard B.; Talley, Nicholas J.; McNabb, Warren C.; Roy, Nicole C. (Frontiers in Cellular and Infection Microbiology, 2020)
The human gastrointestinal tract harbors most of the microbial cells inhabiting the body, collectively known as the microbiota. These microbes have several implications for the maintenance of structural integrity of the gastrointestinal mucosal barrier, immunomodulation, metabolism of nutrients, and protection against pathogens. Dysfunctions in these mechanisms are linked to a range of conditions in the gastrointestinal tract, including functional gastrointestinal disorders, ranging from irritable bowel syndrome, to functional constipation and functional diarrhea. Irritable bowel syndrome is characterized by chronic abdominal pain with changes in bowel habit in the absence of morphological changes. Despite the high prevalence of irritable bowel syndrome in the global population, the mechanisms responsible for this condition are poorly understood. Although alterations in the gastrointestinal microbiota, low-grade inflammation and immune activation have been implicated in the pathophysiology of functional gastrointestinal disorders, there is inconsistency between studies and a lack of consensus on what the exact role of the microbiota is, and how changes to it relate to these conditions. The complex interplay between host factors, such as microbial dysbiosis, immune activation, impaired epithelial barrier function and motility, and environmental factors, including diet, will be considered in this narrative review of the pathophysiology of functional gastrointestinal disorders.